Primary sequence of the envelope glycoprotein of a dengue type 2 virus isolated from patient with dengue hemorrhagic fever and encephalopathy - Sistayanarain A. (2014)
Dengue viruses exist in nature as a collection of highly similar but not identical members (quasispecies). In order to correlate the presence of viral quasispecies with rare occurrence of unusual clinical manifestations in dengue-infected individuals, a dengue type 2 virus was isolated from the peripheral blood of a 12-year-old boy who presented with fever, headache, drowsiness and tonic seizure of the left arm, and subsequently manifested symptoms and signs of dengue hemorrhagic fever. Analysis of the envelope glycoprotein sequence of the encephalopathy-associated virus and two other dengue type 2 viruses from the same epidemic season in Chiang Mai, Thailand revealed that all three viruses belonged to the subtype IIIa of the five-subtype phylogenetic nomenclature system for dengue type 2 virus. The encephalopathy-associated dengue virus was more divergent from the others and was characterized by an Ala-->Val substitution at the position 173 of the envelope glycoprotein. This substitution mapped to the central domain 1 which was not known to be involved directly in envelope-receptor interaction.